ADVANCES AND APPLICATIONS OF INSECT GENETICS AND GENOMICS - Mahmoud Abbas Ali, Islam M. Abdellah; Mohamed R. Eletmany (Chelonian Research Foundation, 2022)
Insects have immense ecological, agricultural, and medical importance. From pollinators to pests [1], insects impact ecosystems, food production, and human health [2]. Their small size and rapid generations also make them invaluable model organisms. Understanding insect genetics is thus crucial, both to gain fundamental biological knowledge and to inform applications like agricultural biotechnology and disease control [3]. Rapid advances in DNA sequencing and genome editing now enable detailed characterization and manipulation of insect genes. Hundreds of insect genomes have been sequenced, allowing comparative genomic analysis of evolution and function. Tools like CRISPR also permit targeted editing of genes to analyze phenotypes or alter traits [2]. However, along with opportunities, these powerful and rapidly advancing genetic capabilities also pose risks of unintended consequences if applied carelessly. This review summarizes major developments in insect genetics and genomics, highlighting key applications as well as important ethical, ecological, and regulatory considerations.